Synthesis and biological evaluation of novel benzothiazole derivatives as potential anticancer and antiinflammatory agents - Xu, Xuemei; Zhu, Zhaojingtao; Chen, Siyu; Fu, Yanneng; Zhang, Jinxia; Guo, Yangyang; Xu, Zhouyang; Xi, Yingying; Wang, Xuebao; Ye, Faqing; Chen, Huijun; Yang, Xiaojiao (Frontiers in Chemistry, 2024)
Cancer, a significant global health concern, necessitates innovative treatments. The pivotal role of chronic inflammation in cancer development underscores the urgency for novel therapeutic strategies. Benzothiazole derivatives exhibit promise due to their distinctive structures and broad spectrum of biological effects. This study aims to explore new anti-tumor small molecule drugs that simultaneously anti-inflammatory and anticancer based on the advantages of benzothiazole frameworks. Drawing inspiration from the structures of benzothiazole derivatives, we designed and synthesized four novel categories of these compounds. Following structural validation, we conducted cell proliferation assays and assessed their anti-inflammatory properties. Our screening process identified a promising candidate, which underwent further scrutiny via various biological assays, encompassing apoptosis, cell cycle progression, cell migration, and Western blot analyses. The results elucidated that nearly all compounds demonstrated significant antiproliferative and anti-inflammatory properties with minimal cytotoxicity. Remarkably, 6-chloro-N-(4-nitrobenzyl) benzo[d]thiazol-2-批注 [81]: Accepted reviewer 1's suggestion to add the word "anti-inflammatory" to the title. amine (compound B7) notably suppressed the proliferation of A431, A549, and H1299 cancer cells while concurrently attenuating IL-6 and TNF-α activities. Subsequent biological assessments unveiled B7's capability to impede cell migration; at concentrations of 1, 2, and 4 μM, B7 exhibited pro-apoptotic effects akin to the lead compound 7-chloro-N-(2,6-dichlorophenyl) benzo[d]thiazol-2-amine (compound 4i) and induced cell cycle arrest in A549 and A431 cells. Western blot analysis corroborated B7's concurrent suppression of AKT and ERK signaling pathways in A431 and A549 cells. These findings suggest that the efficacy of B7 in both antiinflammatory and anticancer capacities may stem from its simultaneous inhibition of the AKT and ERK pathways, thus offering a promising avenue for further biological exploration of benzothiazole derivatives.